2016
DOI: 10.2495/dne-v11-n3-438-446
|View full text |Cite
|
Sign up to set email alerts
|

Should EU land use and land cover data be managed with a NOSQL document store?

Abstract: Land cover (LC) is a scientific landscape classification based on physical properties of earth materials. This information is usually retrieved through remote sensing techniques (e.g. forest cover, urban, clay content, among others). In contrast, Land use (LU) is defined from an anthropocentric point of view. It describes how a specific area is used (e.g. it is usual to indicate whether a territory supports an intensive, extensive use or it is unused). Both geospatial layers are essential inputs in many socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…Here, the table-based layout is able to insert the test-data more than twice as fast as the jsonb-layout. These findings contradicts similar studies found in literature [18,23], which report that NoSQL document stores or data types outperform relational layouts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Here, the table-based layout is able to insert the test-data more than twice as fast as the jsonb-layout. These findings contradicts similar studies found in literature [18,23], which report that NoSQL document stores or data types outperform relational layouts.…”
Section: Discussioncontrasting
confidence: 99%
“…Another important aspect of a database used for managing open geospatial data is usability. Navarro-Carrión et al [18] noted that the query syntax used for the PostgreSQL JSON data type is "somewhat convoluted", an assessment we find to hold true (see Fig. 1 for an example).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…As mentioned above, the SIOSE database is designed according to an object-oriented model, but due to practical reasons, it is adopted and implemented within an object-relational database, which is a clear example of the object-relational impedance mismatch [23]. The usability problem investigated by the SIOSE-INNOVA project has to deal with the fact that regular users of this type of information layers usually work with ESRI Shapefiles and these are generally not used to work with such information in any of the original distributions of SIOSE (corporate databases).…”
Section: The Siose-innova Projectmentioning
confidence: 99%
“…A sophisticated computational experience using SIOSE data was described in detail in [23]. In this case, developed in 2016, an experiment was carried out in which it was verified that specific queries to the SIOSE database could be expedited if the data were stored in a document-oriented database (document store).…”
Section: Benchmarking Sql and Nosql Database Modelsmentioning
confidence: 99%